(untitled) (Research, Society and Development, 2022)
COVID-19 is a viral infectious disease transmitted by the agent SARS-CoV-2. Despite having emerged in December 2019 in the village of Wuhan, China, as isolated cases of pneumonia, in February 2020 it was designated by the World Health Organization (WHO) as a Public Health Emergency of International Concern (PHEIC), and two months later, as a pandemic. Its main clinical manifestations involve classic findings of flu syndrome, such as cough, fatigue, chills and fever. However, it is related to a series of systemic complications, one of the main ones being Severe Acute Respiratory Syndrome (SARS). Therefore, the objective of this study was to analyze the evolution of COVID-19 cases in the municipality of Alagoinhas-BA, between the years 2020-2021, regarding the variables of new confirmed cases, cures and deaths. For this, a search was carried out for updated data regarding such indicators on the electronic address of the Municipal Health Department of the described location. Among the results presented are Table 1, based on the findings, and the 10 graphs distributed throughout this work, which portray the evolution of its main indicators. Through this study, an analysis can be established about the evolution of COVID-19 in the municipality of Alagoinhas-BA, being of great importance to the scientific community. Thus, the results presented here must be taken into account by municipal bodies when making decisions regarding local public health.